Efeito de simbiótico em juvenis de tambatinga (Colossoma macropomum x Piaractus brachypomus) após desafios com Salmonella Schwarzengrund - Santos, Marya Karollyne Tondato (2024)
Brazilian production of farmed fish grew by 4.7% in 2021, which, according to the Brazilian Fish Farming Association (PEIXEBR), demonstrated that year after year the activity has been surpassing the macroeconomic scenario. Among native fish, the Tambatinga hybrid results from the crossing of the female of Tambaqui (Colossoma macropomum) and the male of Pirapitinga (Piaractus brachypomus) and has stood out for presenting greater rusticity and growth, when compared to its parents. To optimize fish production, studies with additives have been widely used due to their diverse functionalities, one of which would be their role as aids in restoring the microbial flora of the animals, digestive tract, reducing the number of pathogenic or undesirable microorganisms. Salmonella enterica serotypes are te main causes of food outbreaks in humans in Brazil and Around the world, having the capacity to colonize seceral animal hosts, including fish. Contamination by Salmonella spp. It occurs via the orofecal route, promoting risks of harm to public health and economic losses in the productive sector of native round fish in Brazil. Therefore, the present research aimed to evaluate the effect of symbiotic on juvenile tambatinga (Colossoma macropomum x Piaractus brachypomus) after challenges due to cohabitation with Salmonella Schwarzengrund. We used 72 tambatinga juveniles with an initial weight of 61.47g ± 1.33g, randomly distributed in 9 polyethylene boxes with a capacity of 130 liters and a useful volume of 110 liters, totaling 8 animals per experimental unit. During the 80-day experimental period, the animals were fed extruded commercial feed with 32% crude protein (CP), divided into three treatments: T0: control (commercial feed without addition of synbiotic); T2: control diet supplemented with 2g of synbiotic/kg of feed; T3: control diet supplemented with 4g of synbiotic/kg of feed. After 30 days of supplementation, the animals were placed in an environment artificially contaminated with Salmonella Schwarzengrund [103 UFC] for a period of 10 minutes. During the research, animal performance indices, immunological and microbiological parameters were analyzed to identify Salmonella Schwarzengrund. The experimental design used was completely randomized (DIC) with 3 treatments and 3 replications. At the end, the data obtained were subjected to analysis of variance (ANOVA) and comparisons of means were carried out using the Tukey test (5%). Fisher's Exact Test was performed to verify the association between the use of synbiotics and the reduction of Salmonella in the gastrointestinal tract. Finally, chi-square (ꭙ2) was performed to calculate the comparison of proportions between control groups (without addition of synbiotic), 2g of synbiotic/kg of feed and 4g of synbiotic/kg of feed. The inclusion of the synbiotic for 80 days, regardless of concentration, did not affect the performance of juvenile tambatinga hybrids, but at a concentration of 4g of synbiotic/kg of feed, it increased the respiratory activity of leukocytes after bacterial inoculation, improving the immune system.